The Moderating Effect of Politically Connected Boards on The Relationship Between Board Characteristics and Earnings Management - Septiany, Sheila; Jurnali, Teddy; Wati, Erna; Pertiwi, Juma (Global Financial Accounting Journal, 2023)
This research aims to test the effect of board characteristics on earnings management. Politically connected boards serve as a moderation variable that affects the relationship of board ownership to earnings management. This research used a quantitative approach and panel regression analysis method. The population of this research used data from companies listed on the Indonesia Stock Exchange (BEI) from 2016 to 2020. The study used a sample of 357 companies. The results revealed that board ownership, board financial expertise, board tenure, politically connected boards, leverage, and board nationality had no significant impact on earnings management. Meanwhile, both firm age and firm size had a significant influence on earnings management practice.